Foreign policy of Kyrgyzstan between Russia and the United States - Namatbekova, Nurzat; Saliev, Kalyynur T. (Linguistics and Culture Review, 2021)
The relevance of the research topic is due to a number of factors. Studying the Central Asian region as a whole, as well as the individual states within it, it is necessary to take into account that this space is a place of intersection of the interests of major world political, economic players, as well as regional powers. The influence of these countries and large multinational corporations can be expressed in a variety of ways, both military and economic, which will be discussed in this article. In addition, it is necessary to take into account a number of challenges to regional (and in the future, global) security, which were either thrown in the past or remain relevant to the present. The purpose of the article is to create a descriptive description of the foreign policy of Kyrgyzstan, which is currently being implemented by the current leadership of the state, in addition, to build a forecast regarding the further steps of the Kyrgyz leadership to build a system of strategic and mutually beneficial cooperation primarily with the Russian Federation and the United States of America.